INVESTIGATION OF THE PURIFICATION PROCESS OF PLATINUM POWDER FROM IMPURITIES - Munosibov, Shokhruh; Usmankulov, Orifjon; Ilkhamov , Murod; Kholdaraliyev , Dilshod (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article presents the results of research on the purification of platinum powder from impurities. The optimal technological parameters were determined based on the results of removing palladium and other non-ferrous metals from the powder by leaching. A new, cost-effective technology for the purification of platinum powder from impurities has been developed. The chemical composition of the purified powder is provided, and formic acid was selected as a reducing agent for palladium oxide prior to its subsequent dissolution in a nitric acid solution. The results of all the tests conducted are presented, the optimal technological parameters for the purification of platinum powder were determined and a new technological scheme for the recovery of platinum powder was developed